The Effect of Dzikir in Reducing Anxiety in Patients Undergoing Modified Radical Mastectomy (MRM) - Khoiriandoh; Betie Febriana; Wahyu Endang (Health and Technology Journal (HTechJ), 2025)
Anxiety is a psychological problem often experienced by preoperative patients, especially in cases of breast cancer requiring major surgery such as Modified Radical Mastectomy (MRM). This condition can increase physiological stress, disrupt hemodynamic stability, slow down the healing process, and even affect prognosis. Non-pharmacological spiritual interventions, such as dzikir, are believed to help patients manage anxiety. This study aims to analyze the effect of dzikir on anxiety levels in preoperative MRM patients at Sultan Agung Islamic Hospital in Semarang. A quantitative study with a one-group pre-test post-test design was conducted on 30 patients who met the inclusion criteria. Anxiety levels were measured using the Depression Anxiety Stress Scale (DASS-42) questionnaire before and after the intervention. Data analysis used a paired t-test with a significance level of 0.05. Patients' anxiety levels before the intervention were in the moderate to severe category, with an average score of 26.4. After receiving dzikir istighfar therapy twice daily over an 8-hour observation period, the average anxiety score decreased to 15.2. The paired t-test showed a significant difference (p = 0.002). Dzikir therapy had a significant effect in reducing the anxiety levels of patients prior to MRM surgery. Dzikir can be used as a complementary intervention in perioperative nursing care, especially in hospitals based on Islamic values.